Hubungan Bermain Peran Dalam Pembelajaran Daring Dengan Tingkat Perkembangan Sosial Emosional Anak Usia Dini - Suprayogi, Muhamad Nanang; Soeriaatmadja, Alya Fadia (Bina Nusantara University, 2024)
This study aims to examine the relationship between role play in online learning and the socio-emotional development level of early childhood. This study uses a quantitative method with 76 respondents from kindergarten and early childhood education teachers in DKI Jakarta. In measuring dramatic play, this study adapts Smilansky's Scale for the Evaluation of Dramatic and Socio-dramatic Play measuring instrument and in measuring social emotional development adapts the Social-emotional development assessment. The data obtained in this study are based on the results of respondents' observations. The results of this study found that there was a significant and positive relationship between role playing and social emotional development level. This is based on the results of the correlation coefficient analysis (r = 0.570, p < 0.05) and the linearity analysis of the scatter plot spreads diagonally on the graph. The result of the study suggests that the teacher can use the role-playing for increasing the development of social-emotional among early childhood.